A fatal case of COVID-19-associated invasive pulmonary aspergillosis. Issue 7 (July 2021) - Iwanaga, Yuto; Kawanami, Toshinori; Yamasaki, Kei; Sakakibara, Hideki; Ikushima, Issei; Ikegami, Hiroaki; Tahara, Masahiro; Akata, Kentaro; Mukae, Hiroshi; Yatera, Kazuhiro
Abstract: A 79-year-old Japanese man with polymyalgia rheumatica was admitted to hospital with coronavirus disease (COVID-19). On admission, he was treated with ciclesonide inhalation, ivermectin, and meropenem. He was intubated 6 days after admission, and methylprednisolone therapy was initiated (1000 mg/day). Hypoxemia and chest radiographic findings temporarily improved. However, chest computed tomography showed bilateral ground-glass attenuations, multiple nodules, and consolidation. Aspergillus fumigatus was cultured from the tracheal aspirate and he was diagnosed with COVID-19-associated invasive pulmonary aspergillosis (CAPA) and treated with liposomal amphotericin B. However, he died 28 days after admission.